The reversal of privatization in China: A political economy perspective - Huang, Zhangkai; Li, Lixing; Ma, Guangrong; Qian, Jun (Journal of Corporate Finance, 2021)
We document reversals of privatization in China—local governments re-possessing ownership stakes in a quarter of previously privatized firms during 1998–2007, a period when the privatization process was still ongoing. This type of ownership restructuring helped ease the unemployment burden in the local labor markets, and was more likely to occur in firms located in provinces led by an official without strong political status in the Chinese Communist Party. A reversal in privatization led to higher leverage, lower profitability and lower labor productivity. Our paper sheds light on how frictions in the political structure affect the implementation of economic policies in a top-down system.